Levin’s Conservation Model And Unpleasant Symptoms Theory In Nursing Care Of Pregnant Women With Preeklamsia : A Case Study: LEVINE’S CONSERVATION MODEL AND UNPLEASANT SYMPTOMS THEORY IN NURSING CARE OF PREGNANT WOMEN WITH PREECLAMPSIA : A CASE STUDY - Nurul Evi; ImamiNur Rachmawati; Tri Budiarti (Jurnal Ilmiah Kesehatan, 2020)
Preeclampsia is a multisystem complication that occurs after 20 weeks of pregnancy and may cause maternal and fetal morbidity and mortality. Preeclampsia is the leading cause of maternal death in many countries.A case studywith the application of Levine’s Conservation and unpleasant symptoms theory on the nursing process of pregnant women with severe preeclampsia.Levine’s conservation theory allows individuals to adapt in order to maintain their integrity with conservation as the final result. The main focus of conservation is a balance between supply and demand of energy, in order to preserve all aspects of individual wholeness.While the unpleasant symptom theory is applied in reducing the symptoms of discomfort by increasing the understanding of aset of symptoms of discomfort from various contexts and providing useful information as well asteaching about the negative effects of them. Keywords: Preeclampsia, Levine’s conservation, Unpleasant symptoms